CHANGES IN THE ORAL MICROFLORA OF PATIENTS WITH CHRONIC LEUKEMIA (International journal of medical sciences, 2025)
Chronic Lymphocytic Leukemia (CLL) is one of the most common neoplastic diseases in clinical practice that belongs to the immunohaematological spectrum and is distinguished by its high degree of heterogeneity. According to research results, not only the clinical course but also the prognosis and mechanisms of response to treatment differ significantly across patients with this disease.The oral cavity microflora is an important biomarker reflecting the internal state of the body; when immunity decreases or against the background of oncohematological diseases, particularly leukemia, the balance of this microflora is disturbed (dysbiosis). This dysbiosis weakens the protective function of the mucosa and increases the susceptibility to the development of inflammation and infection.